Dramat Smierdiakowa - Kruszelnicki, Michał (Przegląd Rusycystyczny, 2017)
This paper offers an interpretation of the figure of Pawel Fyodorovitch Smerdyakov — the fourth of the Karamazov brothers, parricide featured in the last great novel by Fyodor Dostoevsky. The analysis of existing criticism on Smerdyakov, which is my point of departure, invites an assertion that this figure tends to be regarded in almost exclusively negative terms. Looking for answers to the question whence comes this unequivocal evaluation of Smerdyakov, I focus on plot resolutions, the way narration is led, and on the poetics of Smerdyakov’s depictions in the The Brothers Karamazov. I establish that their aim is to fashion from the outset a much revolting image of this particular protagonist. This perspective allows me to state a thesis that is contrary to that of Michail Bakhtin who claimed that the polyphony of Dostoevsky’s oeuvre renders each protagonist’s worldview fully individual and equally valuable and that access to their personalities is granted to us only in so far as they speak of themselves. In a critical discussion with Bakhtin I argue that Smerdyakov functions as an example of an anti-dialogical, that is obscuring the protagonist’s individuality, specifically authorial take aiming to arrest his personality within a predetermined, monological interpretive regime. I then offer a meditation on the ethical message of The Brothers Karamazov which rests on the notion of “the responsibility of everyone for everyone” and I reflect on the reasons why this formula does not apply to the figure of Smerdyakov who, surprisingly, is not treated as a “brother” by anyone in the novel, let alone a human being.